The release of legacy phosphorus from deforestation-derived sediments in shallow, coastal lake Forsyth/Te Roto o Wairewa. Issue 3 (3rd July 2021) - Waters, Sean; Webster-Brown, Jenny G.; Hawes, Ian
ABSTRACT: Phosphorus (P) release from sediments accumulating since catchment deforestation, has been linked to algal blooms which have occurred in Lake Wairewa (Canterbury, NZ) for over a century. However, the mechanisms controlling this internal P loading are poorly understood. To address this issue, we investigated sediment P fractions, P release, dissolved oxygen (DO) and pH at the sediment–water interface, and undertook targeted water sampling. Sediment depth profiles of P fractions indicated surface enrichment (1600 mg P kg −1 ), which was due to an upward flux of P from legacy sediments deposited over at least the last 100 years. Phosphorus release under reducing conditions (0.75–64 mg P m −2  d −1 ) and pH >9.00 (3.27–11.07 mg P m −2  d −1 ) indicated the potential for internal loading. Low DO events (<2 mg L −1 ) in bottom waters were short-lived, and spatially discrete, although longer events (13 days) were observed. pH was variable (6.20–10.80), and prolonged periods of pH >9 (5–6 days) were recorded. Macrophyte beds were key drivers of low DO, elevated pH, and sedimentary P release. The results challenge the paradigm of well mixed shallow lakes and contribute to the knowledge required to understand shallow lake systems impacted by land-use change.